Why study geography? - Parkinson, Alan (Geographer) (Why study series., 2020)
"Considering studying geography at university? Wondering whether a geography degree will get you a good job, and what you might earn? Want to know what it's actually like to study geography at degree level? This book tells you what you need to know. Studying any subject at degree level is an investment in the future that involves significant cost. Now more than ever, students and their parents need to weigh up the potential benefits of university courses. That's where the Why Study series comes in. This series of books, aimed at students, parents and teachers, explains in practical terms the range and scope of an academic subject at university level and where it can lead in terms of careers or further study. Each book sets out to enthuse the reader about its subject and answer the crucial questions that a college prospectus does not."--